Exposure to Violence of Secondary School Children with Visual Impairment - GÜR, KAMER (SAGE PUBLICATIONS INC, 2017)
Although violence is a serious issue that children face all over the world, there is little known about the extent of the violence children with disabilities experience. This study was conducted to identify the frequency of exposure to violence that students with visual impairment experience in any environment, directly or as a witness, and the factors associated with this exposure. The study was conducted as descriptive research at a Secondary School for the Visually Impaired in 2011-2012 with 84 individuals. A questionnaire on demographics, a Violence Exposure Scale, and face-to-face interviews were used as data collection tools. It was found that the large majority of the children with visual impairment in the study had encountered violence on one occasion or more, recently or in the past. The number of students recently exposed to violence was higher than the number of children encountering violence in the past. The mean scores of the students who had recently experienced violence were higher than the scores for exposure to violence in the past. A large majority of the students with visual impairment in the study, all of the boarding students, and most of the day students had been exposed to violence once or more both recently and in the past. It was found that being male, having a congenital visual impairment, and living as a boarding student were risk factors in terms of violence. It may be recommended that school nurses more closely monitor this group of students for signs of violence.
Keywords: violence; visual impairment; student; school nurse; children exposed to domestic violence; violence exposure; DISABILITIES; VICTIMIZATION; STUDENTS